STRATEGI BIMBINGAN KELOMPOK DENGAN TEKNIK MODELLING UNTUK MENINGKATKAN KETERAMPILAN SOSIAL SISWA KELAS X SMAN 10 PANDEGLANG TAHUN AJARAN 2025/2026 - Qurrotul'aini, Dini; Vasco Delano; Fitri Arnita (JCOSE Jurnal Bimbingan dan Konseling, 2025)
Social skills are crucial for students to interact effectively with their environment. Poor social skills can lead to various problems, such as withdrawal, difficulty expressing opinions, and obstacles in the learning process. This study aims to determine the effectiveness of group guidance services with modeling techniques in improving students' social skills. The study used a quantitative approach with a pre-experimental one-group pretest-posttest design. The study population was all 10th-grade high school students, with a purposive sample of 10 students with low social skills. The instrument used was a social skills questionnaire that had been tested for validity and reliability. Data analysis techniques included normality, homogeneity, and Mann-Whitney tests. The results showed a significant difference between pretest and posttest scores, with an Asymp. Sig. value of 0.000 <0.05, indicating that group guidance services with modeling techniques effectively improve students' social skills. The conclusion of this study is that group guidance with modeling techniques can be an alternative strategy for guidance and counseling services in schools to help students develop their social skills.